Evaluation of the MP Rapid 2019-NCOV IgM/IgG combo POCT test vs. an established platform-based method. (July 2021) - Jassam, N; Barth, JH; Allgar, V; Glover, S; Stevenson, F; Lauber, N; Houghton, V; Hanif, Z; Child, J; Clark, B
Background: Accurate and rapid testing for SARS-COV-2 antibodies could improve the diagnosis and management of COVID-19. In this study, we aim to evaluate the diagnostic accuracy of a commercially available point-of-care lateral flow kit independently and in comparison to an established platform-based system. Method: Samples from 144 PCR-confirmed COVID-19 cases and 130 pre-pandemic negative controls were tested in parallel by MP Rapid 2019-NCOV IgM/IgG Combo test and Roche Elecsys. Comparison of results based on serum and capillary blood testing was undertaken. Results: Sensitivity at day 15 onwards was 100% for both methods. Between days 1 and 7 post admission, the IgM/IgG Combo test and Roche Elecsys shown sensitivity of 74% (95% CI : 62%-85%) vs. 67% (95% CI : 55%–79%, P  =   0.3947). Combo test specificities were 100% for IgG, 98.5% for IgM vs. Roche Elecsys specificity of 100%. Concordance analysis showed 98.5% agreement to the Roche Elecsys method (Cohen's Kappa 0.96 95% CI [0.92–0.99]). Capillary blood results showed complete agreement with serum samples using the Combo test. Conclusion: In comparison to Roche Elecsys, our data show that the MP Rapid 2019-NCOV IgM/IgG Combo test provides a high-confidence assay system for the detection of previous exposure to SARS-COV-2 infection with advantage of affording near-patient testing.